VALUASI EKONOMI DAN POTENSI WISATA PANTAI SIGANDU DESA KLIDANG LOR KABUPATEN BATANG - ulfaa, aulia; Ulfa, Aulia Fachreza; Adinugraha, Hendri Hermawan (Bapelitbang Kabupaten Batang, 2024)
Batang Regency is one of the regions in Central Java Province that has several natural attractions that are quite promising if developed. This research is entitled “Economic Valuation and Potential of Tourism Objects at Sigandu Beach, Klidang Lor Village, Batang Regency”, which aims to estimate the total economic value (TEV), analyze the potential level of natural attractions, and analyze the driving factors and inhibiting factors at Sigandu Beach, Batang Regency. This type of research is quantitative using 3 data collection techniques, namely observation, interviews, and documentation. The results of this study reveal that the economic value of a tourist attraction is based on the assessment given from each individual or community to the invaluable enjoyment and costs incurred to visit the tourist attraction. The problems found in Sigandu Beach are garbage and abrasion. Management of tourist areas by maintaining facilities and infrastructure, can improve the tourism economy.